Impressionist & 20th Century Masters. (Zürich : Thomas Ammann Fine Art, 1986)
Cezanne, Paul ; Hodler, Ferdinand ; Brancusi, Constantin ; Leger, Fernand ; Picasso, Pablo ; Severini, Gino ; Beckmann, Max ; Chagall, Marc ; Ernst, Max ; Calder, Alexander ; Giacometti, Alberto ; Balthus ; Bacon, Francis ; Kline, Franz ; Pollock, Jackson
Impressionist & 20th Century Masters, Thomas Ammann Fine Art, Zürich, 1986
Engels
kunstcatalogus